Mg(OH)2 Recovery from Real Bitterns: a Proof of Concept at Pilot Scale - Giuseppe Battaglia; Lorenzo Ventimiglia; Francesco P.M. Viggiano; Fabrizio Vassallo; Andrea Cipollina; Alessandro Tamburini; Giorgio Micale (Chemical Engineering Transactions, 2023)
Water, energy, and minerals are fundamental pillars for the future of humankind. Sustainable and renewable productive processes and resources are the only possibility to face the continuously growing global population and high living standards requirements. The present work introduces a proof of concept for the pilot scale production of magnesium hydroxide, Mg(OH)2, from waste saltworks bitterns located in the district of Trapani, Italy. Mg(OH)2 was produced by adopting a proprietary “Magnesium Crystals Granulometry Controlled Reactor”, Mg-CGCR. The influence of several parameters was investigated on Mg(OH)2 suspensions and powders characteristics: (i) the bittern flow rate, (ii) alkaline sodium hydroxide, NaOH, concentrations solutions (adopted as the precipitant agent) and (iii) the final suspension pH value (stoichiometric or OH- excess amounts). A Mg2+ recovery >99 % can be achieved thanks to the adoption of a product recycling strategy in the reactor. Furthermore, highly pure Mg(OH)2 powders, addressed by cationic purity, were synthesized. Results demonstrate the possibility of producing highly pure Mg(OH)2 products from waste-concentrated saline solutions, thus turning waste into valuable compounds.